2019
DOI: 10.1002/chem.201804802
|View full text |Cite
|
Sign up to set email alerts
|

Complexation and Versatile Reactivity of a Highly Lewis Acidic Cationic Mg Complex with Alkynes and Phosphines

Abstract: [(BDI)Mg+][B(C6F5)4−] (1; BDI=CH[C(CH3)NDipp]2; Dipp=2,6‐diisopropylphenyl) was prepared by reaction of (BDI)MgnPr with [Ph3C+][B(C6F5)4−]. Addition of 3‐hexyne gave [(BDI)Mg+⋅(EtC≡CEt)][B(C6F5)4−]. Single‐crystal X‐ray analysis, NMR investigations, Raman spectra, and DFT calculations indicate a significant Mg‐alkyne interaction. Addition of the terminal alkynes PhC≡CH or Me3SiC≡CH led to alkyne deprotonation by the BDI ligand to give [(BDI‐H)Mg+(C≡CPh)]2⋅2 [B(C6F5)4−] (2, 70 %) and [(BDI‐H)Mg+(C≡CSiMe3)]2⋅2 [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 31 publications
(31 reference statements)
3
38
0
Order By: Relevance
“…25 Although examples of similar BDI γ-C-B bond formation are limited to a recent report by Jones and co-workers, 39 the formation of 5 is clearly also reminiscent of the well documented reactivity of [(BDI)Ae] + and [(BDI)AlMe] + cations towards other unsaturated small molecules such as alkynes or CO 2 . 29,40,41 Consistent with the formulation of the tripodal anion as a bis-imine unit, the N1-C2 (1.2950(19) Å) and N2-C4 (1.293(2) Å) bond lengths of compound 5 are significantly shorter than those observed in unperturbed BDI anions. The geometry about C3 is also effectively tetrahedral, with X-C3-X bond angles in the range of 110.5-119.4°.…”
Section: Resultssupporting
confidence: 54%
“…25 Although examples of similar BDI γ-C-B bond formation are limited to a recent report by Jones and co-workers, 39 the formation of 5 is clearly also reminiscent of the well documented reactivity of [(BDI)Ae] + and [(BDI)AlMe] + cations towards other unsaturated small molecules such as alkynes or CO 2 . 29,40,41 Consistent with the formulation of the tripodal anion as a bis-imine unit, the N1-C2 (1.2950(19) Å) and N2-C4 (1.293(2) Å) bond lengths of compound 5 are significantly shorter than those observed in unperturbed BDI anions. The geometry about C3 is also effectively tetrahedral, with X-C3-X bond angles in the range of 110.5-119.4°.…”
Section: Resultssupporting
confidence: 54%
“…The presence of the central oxygen anions could be through adventitious hydrolysis,t hought he reactioni sr eproducible with yields of around6 8%,o rb yf ixation of molecular oxygen, as has been observed in many other complexes. [14,35] Subsequent experimentsh ave shown that reaction of compound 1 with molecular oxygen via ad rying tube did not produce 3,s uggesting that adventitious moisture is the source of the oxygen atom. The definite point is that such systemsa re able to undergo double small molecule fixation within the same system.…”
Section: Resultsmentioning
confidence: 99%
“…Two distinct types of C−O bonds reside within the structure; namely those of the secondary amide functionality (C 30 −O 1 length of 1.226(2) Å and C 64 −O 2 length of 1.228(2) Å) and those at the centre of the (LiO) 2 core (C 49 −O 4 and C 15 −O 3 bond lengths of 1.357(2) and 1.358(2) Å, respectively). The presence of the central oxygen anions could be through adventitious hydrolysis, though the reaction is reproducible with yields of around 68 %, or by fixation of molecular oxygen, as has been observed in many other complexes . Subsequent experiments have shown that reaction of compound 1 with molecular oxygen via a drying tube did not produce 3 , suggesting that adventitious moisture is the source of the oxygen atom.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations